Caveolin-1 Promoted Collateral Vessel Formation in Patients With Moyamoya Disease - Zhao, Jinbing; Yu, Zhiqiang; Zhang, Yanping; Qiu, Cheng; Zhang, Guangxu; Chen, Lijiu; He, Shengxue; Ma, Jun (Frontiers in Neurology, 2022)
Background Caveolin-1 (Cav-1) plays pivotal roles in the endothelial function and angiogenesis postischemia. Moyamoya disease (MMD) is characterized by progressive artery stenosis with unknown etiology. We aim to determine whether serum Cav-1 levels of patients with MMD were associated with collateral vessel formation after bypass surgery. Methods We studied serum Cav-1 levels of 130 patients with MMD (16 with RNF213 p.R4810K mutation and 114 without RNF213 p.R4810K mutation), 15 patients with acute stroke, and 33 healthy controls. Cerebral perfusion and collateral circulation were evaluated preoperation and at 6 months after operation using pseudocontinuous arterial spin labeling MRI (pCASL-MRI) and digital subtraction angiography (DSA), respectively. Endothelial expression of Cav-1 was verified in the superficial temporal artery (STA) wall of patients with MMD by immunofluorescence double staining. We also investigated whether overexpression of Cav-1 affects cell migration and tube formation using human microvascular endothelial cells (HMECs). Results The serum Cav-1 level of patients with MMD intermediated between the stroke group and healthy controls and it was enhanced after the bypass surgery (681.87 ± 311.63 vs. 832.91 ± 464.41 pg/ml, p = 0.049). By 6 months after bypass surgery, patients with MMD with better collateral compensation manifested higher postoperative/preoperative Cav-1 ratio (rCav-1) than bad compensation patients. Consistently, cerebral blood flow (CBF) determined by pCASL-MRI (nCBFMCA ratio) was positively in line with rCav-1 ratio (r = 0.8615, p < 0.0001). Cav-1 was expressed in the endothelial cells of the STA vessels of patients with MMD. Overexpression of Cav-1 by plasmid transfection in HMECs promoted tube formation and cell migration. Conclusion This study indicated that Cav-1 may be a potential driver to promote angiogenesis and collateral formation after bypass surgery in patients with MMD, providing a better understanding of MMD pathophysiology and potential non-surgical targets of MMD.